Strategi Peningkatan Nilai Jual Produk Inovasi Gula Semut Melalui Pendampingan Pembuatan Sertifikasi Halal Dan P-IRT BPOM di Desa Guntur Macan, Lombok Barat - A’zom, As’ad Humam; Mariani, Putri Ainun; Nabila, Dewi Alya; Jannah, Riadatul; Akbar, Dzofir; Widianty, Desi (Universitas Mataram, 2025)
The innovative processing of palm sugar from the sugar palm tree has great potential as a superior product of Guntur Macan Village, Gunung Sari District, West Lombok Regency, but still faces various challenges, especially in terms of legality and marketing. Many business actors in Guntur Macan Village do not yet have LPH halal certification and BPOM distribution permits, which are obstacles in expanding the market and increasing the selling value and competitiveness of products. This community service program aims to improve the understanding and skills of palm sugar business actors in obtaining business legality through a series of activities, such as MSME surveys, socialization, and assistance in making certifications. The results of the activities showed that before the socialization, the majority of business actors did not have permits due to limited knowledge and cost constraints. However, after the socialization, 88.4% of participants understood the importance of business legality, and most considered this program useful in increasing product competitiveness. Further assistance is needed to simplify the licensing process and provide access to capital for business actors so that they can develop more optimally and increase the selling value of palm sugar products.